Stick dog crashes a party ebook - Watson, Tom (Stick Dog, 2018)
Perfect for fans of Big Nate, Diary of a Wimpy Kid, and the previous Stick Dog books, Tom Watson's hilarious series continues with Stick Dog Crashes a Party —a festive adventure complete with cake, ribs, fireworks, and very special guests! IT'S TIME TO PARTY—STICK DOG STYLE! Stick Dog and his hungry pals have found plenty of tasty treats at Picasso Park before. But it's never looked like it does on this dark, dark night. Strings of white lights, colorful fireworks, and an endless buffet of amazing food have transformed the park into a food-snatching wonderland. There's a party going on, and Stick Dog, Mutt, Poo-Poo, Stripes, and Karen are ready to crash it. But how will they do it? It will take a top-notch strategy, some good luck, and a little help from two charming cats to complete their mission. It's another smart, hilarious romp for Stick Dog and his team of strays. Other favorites in the series include Stick Dog Wants a Hot Dog, Stick Dog Chases a Pizza, and many more!